TOʻQIMACHILIK SANOATIDA NAQSHNING TUTGAN OʻRNI - Berdimbetova, A. (SCIENCE and SOCIETY, 2023)
The article provides information about the history of patterns, their functions, their specific characteristics in different periods, as well as their division into types characteristic of their content. In addition, the significance of its role is widely interpreted.